Getting It Across the Finish Line: Publication Rates of Abstracts Presented at a Major Urologic Conference - Pursnani, Suraj; Feiertag, Jacob; Corey, Zachary; Alzubaidi, Ahmad; Lehman, Erik B.; Raman, Jay D. (Urology (Ridgewood, N.J.), 2024)
To identify characteristics of published manuscripts following a regional American Urological Association (AUA) meeting and recognize trends of publication rates over a 13-year timeframe. Abstract submissions to the Mid-Atlantic AUA (MA-AUA) conference from 2008 to 2020 were collected. Manuscripts were searched using abstract titles and authors in a standard fashion using PubMed, Google Scholar, and Google. Characteristic data was collected, including abstract type (podium or poster), abstract category, first author gender, manuscript publication date, and journal of publication. Univariate and multivariate analysis determined association of these variables with manuscript publication. One thousand two hundred fifty-seven abstracts were presented between 2008 and 2020, of which 458 (36%) were published as manuscripts and 799 (64%) were not published. Of the published manuscripts, 55 (12%) were published prior to the conference date and 403 (88%) were published after. Our analysis was limited to the 403 manuscripts published post-meeting and the 799 abstracts that were not published, with N = 1202. Amongst the 403 published post-meeting, the mean time to publication was 14.8months ± 13.2months. Podium presentations had a higher proportion of publications than those of posters (39.4% vs 30.5%, P = .002). There was a statistically significant difference in proportion of publications between years (P = .002). No association was noted between abstract first author gender and publication (38.7% male vs 39.2% female, P = .899). Approximately one-third of presented abstracts from a major urologic conference were published with an average time to publication of 15months. Publication percentage varied significantly between different years. Podium presentations had a higher publication rate compared to nonpodium abstracts.